2009
DOI: 10.1211/jpp/61.03.0002
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps fungi: natural products, pharmacological functions and developmental products

Abstract: Objectives Parasitic Cordyceps fungi, such as Cordyceps sinensis, is a parasitic complex of fungus and caterpillar, which has been used for medicinal purposes for centuries particularly in China, Japan and other Asian countries. This article gives a general idea of the latest developments in C. sinensis research, with regard to the active chemical components, the pharmacological effects and the research and development of products in recent years. Key findings The common names for preparations include DongChon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
119
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 35 publications
0
119
0
1
Order By: Relevance
“…The bioactive properties of the fungus have also been confirmed by pharmacological studies [2][3][4]. It has been used to treat a wide range of conditions, including respiratory, renal, liver, and cardiovascular diseases, hyposexuality, and hyperlipidemia [5][6][7].…”
mentioning
confidence: 99%
“…The bioactive properties of the fungus have also been confirmed by pharmacological studies [2][3][4]. It has been used to treat a wide range of conditions, including respiratory, renal, liver, and cardiovascular diseases, hyposexuality, and hyperlipidemia [5][6][7].…”
mentioning
confidence: 99%
“…2.2 Reagents and chemicals HNO 3 , H 2 O 2 , KH 2 PO 4 and H 2 SO 4 are analytical grade. All aqueous solutions and dilutions were prepared with ultrapure water (18.2 MΩ cm) obtained from an SG Ultra Clear UV Plus system (Wasseraufbereitung und Regenerierstation GmbH, Germany).…”
Section: Apparatusmentioning
confidence: 99%
“…With the development of medical science and the deepening of pharmacology study, the relationship between major or trace elements in natural medicines and pharmacological effect become a new research focus, the analysis of elements and elemental speciation has been more common reported [4][5][6][7] . At the same time, heavy metal pollution in natural medicines has been causing widespread concern [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…sensu lato , including C. guangdongensis, C. gunnii, C. hawkesii, C. kyushuensis, C. militaris, C. takaomontana, Elaphocordyceps ophioglossoides, O. gracilis, O. formosana, O. japonensis, O. longissima, O. sobolifera , and some of their allies have been researched (Li et al 2006b). These fungi related to Cordyceps sensu lato , although maybe not the anamorphic stage of the latter, such as Acremonium implicatum, Mortierella hepiali , and Paecilomyces hepiali , are beneficial and have been developed as health food or medicine for more than 20 years in China (Zhou et al 2009). …”
Section: Introductionmentioning
confidence: 99%